View of the Shikhara of the Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
View of the south-facing side of the shikhara (superstructure) central shrine in the Neelkanth Mahadev Temple. Since the central shrine has undergone renovations, the plinth, wall, and spire portions are in place. The temple is a variety of Latina nagara (mono-spired) shikhara and pancharatha (five vertical offset or projections on each side) in plan. At the plinth level, the kumbha (pot) moulding has been renovated. During this process, the deities on the faces of the kumbha might have been replastered.